Preparation method of medium-entropy alloy and stainless steel explosive welding composite board
By annealing and solid solution treatment of CoCrNi medium-entropy alloy and 316L stainless steel, and using explosion welding technology of low-carbon steel anvil and corrugated cardboard combined with low-explosion speed and high-rising explosives, the problem of preparing composite plates of this material was solved, and the preparation of high-performance medium-entropy alloy and stainless steel composite plates was achieved.
Patent Information
- Application Number
- CN202411783554.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The lack of explosive welding production technology of CoCrNi medium entropy alloy and 316L stainless steel in the prior art makes it difficult to prepare the composite plate of this material.
By annealing the medium-entropy alloy plate, the stainless steel plate is subjected to solid solution treatment, and low-carbon steel anvil and corrugated cardboard are used as explosives and buffer layers on the explosion site, and explosive welding is used to use low-explosion speed and high-rising mixed explosives for explosion welding, realizing the metallurgical connection between the medium-entropy alloy and stainless steel.
The obtained medium entropy alloy and stainless steel explosive welded composite sheet have excellent mechanical properties, the interface bonding rate is greater than 98.8%, and the yield strength and tensile strength are significantly improved, which is suitable for industrial production.
Smart Images

Figure CN119501268A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of metal composite material processing, and specifically provides a method for preparing a medium entropy alloy and stainless steel explosion-welded composite plate, belonging to the field of material forming. Background Art
[0002] Medium-entropy alloys are a new type of high-performance structural and functional integrated metal material that has emerged in recent years. Compared with traditional alloys, medium-entropy alloys have high hardness, high strength, excellent high-temperature oxidation resistance, corrosion resistance and radiation resistance, and therefore have extremely broad application prospects. As a representative of medium-entropy alloys, the equiatomic ratio CoCrNi alloy is currently recognized as an alloy with excellent room temperature mechanical properties and low-temperature mechanical properties. And compared with other medium-entropy and high-entropy alloys, CoCrNi medium-entropy alloys also show better corrosion resistance in HCl solution. However, the higher Co content in the alloy leads to a significant increase in its manufacturing cost, which to a certain extent limits its wide application.
[0003] 316L stainless steel is one of the most common structural materials at present. Due to its excellent mechanical properties and low price, it has been widely used in various fields of industry and daily life. However, as modern industry has higher and higher requirements for material performance, a single metal material is gradually unable to meet the needs of many fields. Therefore, people pay more and more attention to double-layer or multi-layer heterogeneous metal composite materials.
[0004] The CoCrNi medium entropy alloy is compounded with 316L stainless steel to prepare a layered composite material, which can not only give full play to the performance advantages of the CoCrNi medium entropy alloy, but also has the low cost advantage of 316L stainless steel, which is of great significance to promote the wider application of the CoCrNi medium entropy alloy. As an important means of preparing dissimilar metal layered composite materials, the explosive welding method has been applied to the composite of various materials such as copper / aluminum, titanium / aluminum, titanium / steel, titanium / stainless steel, nickel / copper, and nickel / stainless steel. However, as an equal component multi-component alloy, the CoCrNi medium entropy alloy is compared with conventional pure metals such as aluminum, copper, titanium, and nickel, as well as aluminum alloys, copper alloys, titanium alloys, carbon steel, and stainless steel. Due to its disordered atomic arrangement and the absence of main alloying elements, its conventional plastic deformation and the plastic deformation mechanism caused by the explosive composite process are completely different from those of conventional pure metals and alloys. Therefore, there is currently no relevant experience and report on the production technology of explosive welding of CoCrNi medium entropy alloy and 316L stainless steel. It can be seen that the development of a technology that meets the explosive welding of CoCrNi medium entropy alloy and 316L stainless steel is a key problem that needs to be solved in the field of composite plate manufacturing technology. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a method for preparing a composite plate of medium entropy alloy and stainless steel explosive welding. The medium entropy alloy in the composite plate of the present invention is an equiatomic ratio CoCrNi medium entropy alloy, the stainless steel is 316L, and the composite plate is obtained by explosion welding; the explosive welding process uses a low-carbon steel anvil as a backing plate, stainless steel as a substrate, a medium entropy alloy as a composite plate, and corrugated cardboard as a buffer layer between explosives and composite plates, and then a low-detonation velocity and high-intensity mixed explosive is used to achieve metallurgical connection. The process of the present invention is simple and convenient, and is suitable for industrial production.
[0006] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] The invention discloses a method for preparing a medium-entropy alloy and stainless steel explosion-welded composite plate. The method comprises the following steps: subjecting a medium-entropy alloy plate to annealing treatment, subjecting a stainless steel plate to solution treatment, and then laying sand, anvils, stainless steel plates, support columns, medium-entropy alloy plates, corrugated paper, and explosives in sequence from bottom to top on an explosion field. Then, the medium-entropy alloy and stainless steel explosion-welded composite plate is obtained by explosion welding. The explosion velocity of the explosive is 1600-2100 m / s, and the intensity is 15-18 mm.
[0008] In the present invention, the medium entropy alloy plate is first annealed and the stainless steel plate is solution treated so that they both have good plasticity, ensuring that the explosion process can easily achieve metallurgical bonding of the materials without cracking, and then the stainless steel plate is used as the substrate and the medium entropy alloy plate as the composite plate, and finally low detonation velocity and high intensity explosives are used for explosion welding to obtain an explosion with metallurgical bonding, wherein the low detonation velocity can control the amplitude of the composite interface waveform, forming a small wave bonding interface, and improving the bonding strength, while the high intensity explosives can cause the substrate and the composite plate to undergo severe work hardening during the explosion process, thereby improving the strength of the material and compensating for the material strength loss caused by complete annealing before the explosion composite, thereby obtaining a medium entropy alloy and stainless steel explosion welded composite plate with excellent mechanical properties in the present invention.
[0009] As a preferred embodiment, the stainless steel in the stainless steel plate is 316L, and the medium entropy alloy in the medium entropy alloy plate is CoCrNi medium entropy alloy, wherein Co, Cr and Ni are in equal atomic ratios.
[0010] As a preferred embodiment, the length × width × thickness of the stainless steel plate is: (400~1000) mm × (200~500) mm × (5~20) mm; the length × width × thickness of the medium entropy alloy plate is: (410~1010) mm × (210~510) mm × (1.5~3) mm, and the length and width of the medium entropy alloy plate are both greater than the length and width of the stainless steel plate.
[0011] In the present invention, the high-cost medium-entropy alloy plate is selected as a thin plate, and the low-cost stainless steel plate is used as a thick plate. In the process of explosive composite, the stainless steel plate is used as the base plate and the medium-entropy alloy plate is used as the composite plate, which has better support.
[0012] As a preferred solution, the surface roughness Ra of the medium entropy alloy plate and the stainless steel plate is ≤3 μm. In actual operation, the surface of the substrate and the composite plate is polished before use to remove surface oil and oxides to ensure that the surface roughness Ra is ≤3 μm.
[0013] As a preferred solution, the medium entropy alloy plate is annealed at a temperature of 1000-1100°C for 1-2 hours. By completely softening and annealing the medium entropy alloy plate within the above parameters, the alloy has good plasticity, ensuring that the explosion process can easily achieve metallurgical bonding of the material without cracking.
[0014] As a preferred solution, the stainless steel plate is subjected to a solution treatment at a temperature of 1100-1150° C. for 1.5-2 hours. In actual operation, after the solution treatment is completed, a rapid cooling such as water cooling is performed.
[0015] Through the above-mentioned solution treatment, the stainless steel plate is softened and has good plasticity, ensuring that the explosion process can easily achieve metallurgical bonding of the materials without cracking.
[0016] In industrial applications, a hard soil site needs to be selected as a test site, and debris must be removed and leveled to form an explosion site, and then a layer of 8~10mm sand is laid as the foundation.
[0017] As a preferred solution, the thickness of the sand is 8 to 10 mm.
[0018] As a preferred solution, the anvil is made of low-carbon steel and has a thickness of 40-60 mm.
[0019] In the present invention, due to the use of high-strength explosives, the explosion process not only has a greater impact force on the base plate and the composite plate, but also has a greater impact on the anvil plate. Therefore, by placing a low-carbon steel anvil plate with a larger thickness and better toughness under the soft base plate, serious bending and deformation of the composite plate during the explosion process can be avoided.
[0020] As a further preferred embodiment, the anvil is 2000-3000 mm long and 1000-2000 mm wide. In actual industrial applications, the anvil should be parallel to the ground and not tilted, and the upper surface of the anvil should be cleaned and kept smooth, and the stainless steel plate should be placed in the center of the anvil.
[0021] As a preferred solution, support columns are arranged at the four corners of the surface of the stainless steel plate, and the medium entropy alloy plate is placed above the support columns to ensure that the center position of the medium entropy alloy plate and the center position of the stainless steel plate are on the same axis, and the four sides of the medium entropy alloy plate are parallel to the four sides of the stainless steel plate.
[0022] Further preferably, the support column has a diameter of 9-10 mm, preferably 10 mm, and a height of 5-8 mm, preferably 6 mm.
[0023] As a preferred solution, wooden strips are used to surround the medium entropy alloy plate on all sides, and the upper surface of the wooden strips is controlled to be higher than the surface of the medium entropy alloy plate to serve as an explosive pool, and the depth of the explosive pool is 50-70 mm.
[0024] As a preferred solution, the thickness of the corrugated paper is 5-6 mm. In the industrial application process, the corrugated paper is placed in the explosive pool to isolate the explosive from direct contact with the composite board, and plays a role in buffering and protecting the board surface during the explosion, and then the explosive is evenly laid on the corrugated paper.
[0025] As a preferred embodiment, the explosive has the following components, calculated by mass percentage: 50-60% antimony-free rock ammonium nitrate explosive, 10-15% magnesium carbonate powder, 5-10% silicon carbide powder, 5-10% perlite powder, 5-10% charcoal powder, and 5-8% nickel powder.
[0026] Generally, the detonation velocity of explosives is high and the intensity is also large; the detonation velocity is low and the intensity is small, but the detonation velocity is related to the released energy and the temperature rise. Although the intensity is also related to the energy, it is more related to the impact force. In the explosive components of the present invention, antimony-free rock ammonium nitrate is used as the basic explosive. Adding magnesium carbonate and silicon carbide powder to the basic explosive can reduce the detonation velocity of the explosive. Adding perlite powder and charcoal powder can increase the fluffiness, which is conducive to detonation; adding nickel powder can increase the intensity of the explosive, thereby obtaining an explosive with low detonation velocity and high intensity. When the explosives of the components of the present invention are used for production, the characteristics of low detonation velocity can ensure that the composite interface is a small wavy bonding interface, thereby improving the bonding strength; and the characteristics of high intensity can ensure that the base plate and the composite plate undergo severe work hardening during the explosion process, thereby compensating for the material strength loss caused by complete annealing before the explosive composite.
[0027] In industrial applications, the explosives must be prepared, dried, and mixed evenly within 1 hour before use, and then sieved with an 80-mesh sieve, and the -80-mesh mixed powder is selected as the standby explosive. When using, 5% of water by volume must be added to the mixed explosives and mixed evenly before laying.
[0028] As a preferred embodiment, the density of the explosive is 0.75-0.9 g / cm 3 .
[0029] As a preferred solution, a detonator is installed in the explosive, and the detonator is installed at the center of the short side direction of the stainless steel plate and the medium entropy alloy plate, and then a lead is connected to the detonator, and finally the connecting lead is connected to the remote control detonation device, and the detonator is detonated by the detonator through the connecting lead to complete the explosive welding, that is, the medium entropy alloy and stainless steel explosive welded composite plate. The inventor found that arranging the detonator to the short side can improve the yield.
[0030] In a further preferred embodiment, three quarters of the detonator is buried in the explosive.
[0031] In industrial production, the board surface after explosive compounding needs to be cleaned and leveled, and the cracked and collapsed parts of the edges need to be cut off. Finally, ultrasonic flaw detection is used to ensure that the entire board surface is well bonded.
[0032] The medium-entropy alloy and stainless steel explosion-welded composite plate prepared by the present invention has an interface bonding rate greater than 98.8%, a yield strength greater than 620 MPa, a tensile strength greater than 735 MPa, an elongation after fracture greater than 40%, and an interface shear strength greater than 300 MPa.
[0033] The interface bonding rate obtained under the optimal process is 99.2%, the yield strength is 635MPa, the tensile strength is 755MPa, the elongation after fracture is 42%, and the interface shear strength is 318MPa.
[0034] Principles and advantages
[0035] The present invention realizes metallurgical connection between CoCrNi medium entropy alloy and 316L stainless steel through explosive welding, and provides a preparation method of high-performance bimetallic composite plate suitable for industrial production. During explosive welding production, the selection of various parameters of explosive welding plays a vital role in the performance of the final composite plate. After multiple experiments, the present invention explores suitable explosive welding process parameters for CoCrNi medium entropy alloy and 316L stainless steel composite plate with excellent performance.
[0036] Before the explosive welding, the present invention performs a complete annealing treatment on the selected CoCrNi medium entropy alloy and 316L stainless steel, so that the alloy has good plasticity, ensuring that the metallurgical bonding of the materials is easily achieved during the explosion process without cracking. In particular, when high-strength explosives are used in the present invention, the plate to be composited must be pretreated to a suitable state. In industrial production, a low-carbon steel anvil with a large thickness and good toughness is placed under the soft substrate to avoid serious bending deformation of the composite plate during the explosion process. In addition, the use of low-detonation-velocity explosives can control the amplitude of the composite interface waveform to form a small-wave bonding interface. The selection of high-strength explosives can cause severe work hardening of the substrate and the composite plate during the explosion process, improve the strength of the material, and make up for the material strength loss caused by complete annealing before the explosion composite. Therefore, this technology is designed specifically using the excellent work hardening capabilities of the soft CoCrNi medium entropy alloy and 316L stainless steel.
[0037] The present invention obtains a composite plate of a medium entropy alloy and stainless steel by an explosive welding method for the first time. Under the optimal process conditions, the interface bonding rate of the composite plate obtained is 99.2%, the yield strength is 635 MPa, the tensile strength is 755 MPa, the elongation after fracture is 42%, and the interface shear strength is 318 MPa. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 Schematic diagram of the process structure for explosive welding of CoCrNi medium entropy alloy and 316L stainless steel.
[0039] Figure 2 Explosion welding samples of CoCrNi medium entropy alloy and 316L stainless steel.
[0040] Figure 3 The interface morphology of the explosively welded composite plate of the medium entropy alloy and stainless steel obtained in Example 1 shows a small wavy bonding interface. DETAILED DESCRIPTION
[0041] The following are preferred embodiments of the present invention, but not all embodiments. Without departing from the principle of the process innovation, any equivalent process transformation made by using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, shall be deemed as the patent protection scope of the present invention.
[0042] Example 1
[0043] Select the CoCrNi medium entropy alloy sheet with equal atomic ratio and 316L stainless steel sheet as raw materials. First, the CoCrNi medium entropy alloy sheet is subjected to complete softening annealing at 1000℃ / 2h, and the 316L stainless steel is subjected to solid solution + rapid cooling at 1100℃ / 2h. Then, the following steps are implemented:
[0044] S1. Cut out stainless steel plates with the dimensions of 400 mm × 200 mm × 5 mm in length × width × thickness and CoCrNi medium-entropy alloy plates with the dimensions of 410 mm × 210 mm × 1.5 mm respectively; use a sanding belt to grind the surfaces of the two alloy plates to remove surface oil stains and oxides.
[0045] S2. Select a hard soil site as the blasting site, remove debris from the site, level it, and then lay a layer of 8~10mm sand as the foundation.
[0046] S3. Place a low-carbon steel anvil with dimensions of 1000mm×2000mm×40mm parallel to the ground on the foundation and clean its surface.
[0047] S4. Place a 5 mm thick stainless steel plate as a substrate in the center area of the anvil.
[0048] S5. Arrange four aluminum alloy columnar support columns with a diameter of 10 mm and a height of 6 mm at the four corners of the stainless steel plate surface.
[0049] S6. Place the CoCrNi medium-entropy alloy plate on the support column, and ensure that the center position of the medium-entropy alloy and the center position of the stainless steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.
[0050] S7. Surround the medium-entropy alloy with wooden strips, the upper surface of the wooden strips is 50 mm higher than the surface of the medium-entropy alloy, forming an explosive pool with a depth of 50 mm.
[0051] S8. Lay a layer of 5mm corrugated paper at the bottom of the explosives pool to isolate the explosives from direct contact with the composite plate. At this time, the depth of the explosives pool is 45mm.
[0052] S9. Evenly spread the homemade low-detonation-velocity and high-strength mixed explosive in the explosive pool above the corrugated paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is as follows by mass percentage: 50% antimony-free rock ammonium nitrate explosive, 15% magnesium carbonate powder, 10% silicon carbide powder, 10% perlite powder, 10% charcoal powder, and 5% nickel powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved with an 80-mesh sieve, and the -80-mesh mixed powder is selected as the stand-by explosive. Add 5% by volume of water to the mixed explosive before use and mix evenly. The detonation velocity of the mixed explosive is 1600m / s, the strength is 15mm, and the density is 0.75g / cm 3 .
[0053] S10. Detonate the detonator with a detonator through the connecting wire to obtain a medium-entropy alloy and stainless steel composite plate.
[0054] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.
[0055] The interface bonding rate of the medium-entropy alloy and stainless steel explosion-welded composite plate prepared by the present implementation process is 99%, the yield strength is 625 MPa, the tensile strength is 742 MPa, the elongation after fracture is 46.2%, and the interface shear strength is 312 MPa.
[0056] Example 2
[0057] Select the CoCrNi medium entropy alloy sheet with equal atomic ratio and 316L stainless steel sheet as raw materials. First, the CoCrNi medium entropy alloy sheet is subjected to complete softening annealing at 1000℃ / 2h, and the 316L stainless steel is subjected to solid solution + rapid cooling at 1100℃ / 2h. Then, the following steps are implemented:
[0058] S1. Cut out stainless steel plates with the dimensions of 600 mm × 300 mm × 15 mm in length × width × thickness and CoCrNi medium-entropy alloy plates with the dimensions of 610 mm × 310 mm × 2 mm respectively; use a sanding belt to grind the surfaces of the two alloy plates to remove surface oil stains and oxides.
[0059] S2. Select a hard soil site as the blasting site, remove debris from the site, level it, and then lay a layer of 8~10mm sand as the foundation.
[0060] S3. Place a low-carbon steel anvil with dimensions of 2000mm×2500mm×50mm parallel to the ground on the foundation and clean its surface.
[0061] S4. Place a 15 mm thick stainless steel plate as a substrate in the center area of the anvil.
[0062] S5. Arrange four aluminum alloy columnar support columns with a diameter of 10 mm and a height of 6 mm at the four corners of the stainless steel plate surface.
[0063] S6. Place the CoCrNi medium-entropy alloy plate on the support column, and ensure that the center position of the medium-entropy alloy and the center position of the stainless steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.
[0064] S7. Surround the medium-entropy alloy with wooden strips, the upper surface of the wooden strips is 60 mm higher than the surface of the medium-entropy alloy, forming an explosive pool with a depth of 60 mm.
[0065] S8. Lay a layer of 5mm corrugated paper at the bottom of the explosives pool to isolate the explosives from direct contact with the composite plate. At this time, the depth of the explosives pool is 55mm.
[0066] S9. Evenly spread the homemade low-detonation-velocity and high-strength mixed explosive in the explosive pool above the corrugated paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is as follows by mass percentage: 54% antimony-free rock ammonium nitrate explosive, 10% magnesium carbonate powder, 10% silicon carbide powder, 10% perlite powder, 10% charcoal powder, and 6% nickel powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved with an 80-mesh sieve, and the -80-mesh mixed powder is selected as the stand-by explosive. Add 5% by volume of water to the mixed explosive before use and mix evenly. The detonation velocity of the mixed explosive is 1800m / s, the strength is 16mm, and the density is 0.80g / cm 3 .
[0067] S10. Detonate the detonator with a detonator through the connecting wire to obtain a medium-entropy alloy and stainless steel composite plate.
[0068] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.
[0069] The interface bonding rate of the medium-entropy alloy and stainless steel explosion-welded composite plate prepared by the present implementation process is 99.2%, the yield strength is 635 MPa, the tensile strength is 755 MPa, the elongation after fracture is 42%, and the interface shear strength is 318 MPa.
[0070] Example 3
[0071] Select the CoCrNi medium entropy alloy sheet with equal atomic ratio and 316L stainless steel sheet as raw materials. First, the CoCrNi medium entropy alloy sheet is subjected to complete softening annealing at 1000℃ / 2h, and the 316L stainless steel is subjected to solid solution + rapid cooling at 1100℃ / 2h. Then, the following steps are implemented:
[0072] S1. Cut out stainless steel plates with the dimensions of 1000 mm × 500 mm × 20 mm in length × width × thickness and CoCrNi medium-entropy alloy plates with the dimensions of 1010 mm × 510 mm × 3 mm respectively; use a sanding belt to grind the surfaces of the two alloy plates to remove surface oil stains and oxides.
[0073] S2. Select a hard soil site as the blasting site, remove debris from the site, level it, and then lay a layer of 8~10mm sand as the foundation.
[0074] S3. Place a low-carbon steel anvil with dimensions of 2000mm×3000mm×60mm parallel to the ground on the foundation and clean its surface.
[0075] S4. Place a 20 mm thick stainless steel plate as a substrate in the center area of the anvil.
[0076] S5. Arrange four aluminum alloy columnar support columns with a diameter of 10 mm and a height of 6 mm at the four corners of the stainless steel plate surface.
[0077] S6. Place the CoCrNi medium-entropy alloy plate on the support column, and ensure that the center position of the medium-entropy alloy and the center position of the stainless steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.
[0078] S7. Surround the medium-entropy alloy with wooden strips, the upper surface of the wooden strips is 70 mm higher than the surface of the medium-entropy alloy, forming an explosive pool with a depth of 70 mm.
[0079] S8. Lay a layer of 5mm corrugated paper at the bottom of the explosives pool to isolate the explosives from direct contact with the composite plate. At this time, the depth of the explosives pool is 65mm.
[0080] S9. Evenly spread the homemade low-detonation-velocity and high-strength mixed explosive in the explosive pool above the corrugated paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is as follows by mass percentage: 60% antimony-free rock ammonium nitrate explosive, 15% magnesium carbonate powder, 5% silicon carbide powder, 5% perlite powder, 7% charcoal powder, and 8% nickel powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved with an 80-mesh sieve, and the -80-mesh mixed powder is selected as the stand-by explosive. Add 5% by volume of water to the mixed explosive before use and mix evenly. The detonation velocity of the mixed explosive is 2100m / s, the strength is 18mm, and the density is 0.90g / cm 3 .
[0081] S10. Detonate the detonator with a detonator through the connecting wire to obtain a medium-entropy alloy and stainless steel composite plate.
[0082] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.
[0083] The interface bonding rate of the medium-entropy alloy and stainless steel explosion-welded composite plate prepared by the present implementation process is 98.8%, the yield strength is 622 MPa, the tensile strength is 731 MPa, the elongation after fracture is 40.3%, and the interface shear strength is 304 MPa.
[0084] Example 4
[0085] Select the CoCrNi medium entropy alloy sheet with equal atomic ratio and 316L stainless steel sheet as raw materials. First, the CoCrNi medium entropy alloy sheet is subjected to complete softening annealing at 1000℃ / 2h, and the 316L stainless steel is subjected to solid solution + rapid cooling at 1100℃ / 2h. Then, the following steps are implemented:
[0086] S1. Cut out stainless steel plates with the dimensions of 750 mm × 400 mm × 10 mm in length × width × thickness and CoCrNi medium-entropy alloy plates with the dimensions of 760 mm × 410 mm × 2 mm respectively; use a sanding belt to grind the surfaces of the two alloy plates to remove surface oil stains and oxides.
[0087] S2. Select a hard soil site as the blasting site, remove debris from the site, level it, and then lay a layer of 8~10mm sand as the foundation.
[0088] S3. Place a low-carbon steel anvil with dimensions of 1500mm×2000mm×50mm parallel to the ground on the foundation and clean its surface.
[0089] S4. Place a 10 mm thick stainless steel plate as a substrate in the center area of the anvil.
[0090] S5. Arrange four aluminum alloy columnar support columns with a diameter of 10 mm and a height of 6 mm at the four corners of the stainless steel plate surface.
[0091] S6. Place the CoCrNi medium-entropy alloy plate on the support column, and ensure that the center position of the medium-entropy alloy and the center position of the stainless steel substrate are on the same axis, and the four sides are parallel to the four sides of the substrate.
[0092] S7. Surround the medium-entropy alloy with wooden strips, the upper surface of the wooden strips is 65 mm higher than the surface of the medium-entropy alloy, forming an explosive pool with a depth of 65 mm.
[0093] S8. Lay a layer of 5mm corrugated paper at the bottom of the explosives pool to isolate the explosives from direct contact with the composite plate. At this time, the depth of the explosives pool is 60mm.
[0094] S9. Evenly spread the homemade low-detonation-velocity and high-strength mixed explosive in the explosive pool above the corrugated paper, and arrange the detonating cap at the center of one of the short sides to ensure that three-quarters of the detonating cap is buried in the explosive. In this embodiment, the composition of the explosive is as follows by mass percentage: 56% antimony-free rock ammonium nitrate explosive, 15% magnesium carbonate powder, 7% silicon carbide powder, 7% perlite powder, 8% charcoal powder, and 7% nickel powder. All powders are dried and mixed evenly within 1 hour before use, and then sieved with an 80-mesh sieve, and the -80-mesh mixed powder is selected as the stand-by explosive. Before use, add 5% by volume of water to the mixed explosive and mix it evenly. The detonation velocity of the mixed explosive is 2000m / s, the strength is 17mm, and the density is 0.89g / cm 3 .
[0095] S10. Detonating the detonator through the connecting wire and the detonator to obtain a composite plate of the medium entropy alloy and the stainless steel.
[0096] The resulting explosion-welded plates were surface cleaned, leveled, and the edge cracks and collapsed parts were removed, and finally ultrasonic flaw detection was performed.
[0097] The interface bonding rate of the medium-entropy alloy and stainless steel explosion-welded composite plate prepared by the present implementation process is 99.1%, the yield strength is 630 MPa, the tensile strength is 726 MPa, the elongation after fracture is 41.6%, and the interface shear strength is 312 MPa.
[0098] Comparative Example 1
[0099] The other conditions are the same as those in Example 1, except that the CoCrNi medium-entropy alloy is not annealed before the explosive composite, that is, the composite plate material is a hard CoCrNi medium-entropy alloy. Since the hard medium-entropy alloy has high strength and poor plasticity, it cannot withstand strong plastic deformation during the explosive composite process. Therefore, after the explosion, the medium-entropy alloy composite plate is cracked due to the strong impact force generated by the explosives, and the composite fails.
[0100] Comparative Example 2
[0101] The other conditions are the same as those in Example 1, except that the explosive composition is changed to: 55% of antimony-free rock ammonium nitrate explosive, 15% of magnesium carbonate powder, 10% of silicon carbide powder, 10% of perlite powder, and 10% of charcoal powder. That is, no Ni powder is added to the explosive. Since the role of nickel in the modified explosive is to increase the explosive strength, after the nickel powder is not added, the explosive is a low-detonation-velocity and low-strength explosive. Although the low strength is beneficial to the surface quality after the composite, the impact force provided by the explosion process is insufficient due to the low strength, and the cross-sectional bonding rate after the explosion composite is only 20%.
Claims
1. A method for preparing a composite plate of medium entropy alloy and stainless steel by explosive welding, characterized in that: The medium entropy alloy plate is annealed, the stainless steel plate is solution treated, and then sand, anvils, stainless steel plates, support columns, medium entropy alloy plates, corrugated paper, and explosives are laid in sequence from bottom to top on the explosion field, and then explosion welding is performed to obtain a medium entropy alloy and stainless steel explosion welded composite plate, wherein the detonation velocity of the explosive is 1600-2100 m / s, and the intensity is 15-18 mm.
2. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1, characterized in that: The stainless steel in the stainless steel plate is 316L, and the medium entropy alloy in the medium entropy alloy plate is CoCrNi medium entropy alloy, wherein Co, Cr and Ni are in equal atomic ratios; The length×width×thickness of the stainless steel plate is: 400~1000mm×200~500mm×5~20mm; the length×width×thickness of the medium entropy alloy plate is: 410~1010mm×210~510mm×1.5~3mm, and the length and width of the medium entropy alloy plate are greater than the length and width of the stainless steel plate; The surface roughness Ra of the medium entropy alloy plate and the stainless steel plate are both ≤3 μm.
3. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1 or 2, characterized in that: The medium entropy alloy plate is annealed at a temperature of 1000-1100° C. and for a time of 1-2 h.
4. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1 or 2, characterized in that: The stainless steel plate is subjected to a solution treatment, wherein the temperature of the solution treatment is 1100-1150° C. and the time of the solution treatment is 1.5-2 hours.
5. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1 or 2, characterized in that: The thickness of the sand is 8-10 mm; The material of the anvil is low carbon steel, and the thickness of the anvil is 40-60 mm; The anvil has a length of 2000-3000 mm and a width of 1000-2000 mm.
6. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1 or 2, characterized in that: Arrange support columns at the four corners of the surface of the stainless steel plate, and then place the medium entropy alloy plate on the support columns to ensure that the center position of the medium entropy alloy plate and the center position of the stainless steel plate are on the same axis, and the four sides of the medium entropy alloy plate are parallel to the four sides of the stainless steel plate; The support column has a diameter of 9-10 mm and a height of 5-8 mm.
7. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1 or 2, characterized in that: The medium entropy alloy plate is surrounded by wooden strips, and the upper surface of the wooden strips is controlled to be higher than the surface of the medium entropy alloy plate to serve as an explosive pool, and the depth of the explosive pool is 50-70 mm; The thickness of the corrugated paper is 5-6 mm.
8. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1 or 2, characterized in that: The explosive has the following composition by mass percentage: 50-60% antimony-free rock ammonium nitrate explosive, 10-15% magnesium carbonate powder, 5-10% silicon carbide powder, 5-10% perlite powder, 5-10% charcoal powder, and 5-8% nickel powder; The density of the explosive is 0.75-0.9 g / cm 3 .
9. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1 or 2, characterized in that: A detonator is installed in the explosive, the detonator is installed at the center position of the short side direction of the stainless steel plate and the medium entropy alloy plate, and then a lead is connected to the detonator, and finally the connecting lead is connected to a remote control detonating device, and the detonator is detonated by a detonator through the connecting lead to complete the explosive welding, so as to obtain a medium entropy alloy and stainless steel explosive welded composite plate; three quarters of the detonator is buried in the explosive.
10. The method for preparing a medium entropy alloy and stainless steel explosively welded composite plate according to claim 1 or 2, characterized in that: The interface bonding rate of the medium entropy alloy and stainless steel explosion-welded composite plate is greater than 98.8%, the yield strength is greater than 620 MPa, the tensile strength is greater than 735 MPa, the elongation after fracture is greater than 40%, and the interface shear strength is greater than 300 MPa.
Citation Information
Patent Citations
Big-board TU1 / Q235B explosive welding high-strength conductive composite plate
CN102151977A
Light high-strength high-corrosion-resistance titanium / aluminum / titanium double-vertical-explosion welding three-layer composite material
CN106944736A
Low-detonation-velocity emulsified explosive and application thereof
CN107200670A
Explosive welding method for manufacturing composite plate from C-276 alloy
CN109434267A
CoCrNiSi medium-entropy alloy and preparation method thereof
CN111876648A
Cited By
Preparation method of bimetal composite seamless tube
CN120055735A
Large-size tin-phosphor bronze / Q235B composite board and preparation method thereof
CN121649545A
4J29 kovar alloy / 304 stainless steel composite board and preparation method thereof
CN121649700A
4j29 covar alloy / 304 stainless steel clad plate and preparation method thereof
CN121649700B